Purification and functional characterisation of rhiminopeptidase A, a novel aminopeptidase from the venom of Bitis gabonica rhinoceros. - Sakthivel Vaiyapuri; Simon C Wagstaff; Kimberley A Watson; Robert A Harrison; Jonathan M Gibbins; E Gail Hutchinson (PLoS Neglected Tropical Diseases)
Background Snake bite is a major neglected public health issue within poor communities living in the rural areas of several countries throughout the world. An estimated 2.5 million people are bitten by snakes each year and the cost and lack of efficacy of current anti-venom therapy, together with the lack of detailed knowledge about toxic components of venom and their modes of action, and the unavailability of treatments in rural areas mean that annually there are around 125,000 deaths worldwide. In order to develop cheaper and more effective therapeutics, the toxic components of snake venom and their modes of action need to be clearly understood. One particularly poorly understood component of snake venom is aminopeptidases. These are exo-metalloproteases, which, in mammals, are involved in important physiological functions such as the maintenance of blood pressure and brain function. Although aminopeptidase activities have been reported in some snake venoms, no detailed analysis of any individual snake venom aminopeptidases has been performed so far. As is the case for mammals, snake venom aminopeptidases may also play important roles in altering the physiological functions of victims during envenomation. In order to further understand this important group of snake venom enzymes we have isolated, functionally characterised and analysed the sequence-structure relationships of an aminopeptidase from the venom of the large, highly venomous West African gaboon viper, Bitis gabonica rhinoceros. Methodology and principal findings The venom of B. g. rhinoceros was fractionated by size exclusion chromatography and fractions with aminopeptidase activities were isolated. Fractions with aminopeptidase activities showed a pure protein with a molecular weight of 150 kDa on SDS-PAGE. In the absence of calcium, this purified protein had broad aminopeptidase activities against acidic, basic and neutral amino acids but in the presence of calcium, it had only acidic aminopeptidase activity (APA). Together with the functional data, mass spectrometry analysis of the purified protein confirmed this as an aminopeptidase A and thus this has been named as rhiminopeptidase A. The complete gene sequence of rhiminopeptidase A was obtained by sequencing the PCR amplified aminopeptidase A gene from the venom gland cDNA of B. g. rhinoceros. The gene codes for a predicted protein of 955 amino acids (110 kDa), which contains the key amino acids necessary for functioning as an aminopeptidase A. A structural model of rhiminopeptidase A shows the structure to consist of 4 domains: an N-terminal saddle-shaped beta domain, a mixed alpha and beta catalytic domain, a beta-sandwich domain and a C-terminal alpha helical domain. Conclusions This study describes the discovery and characterisation of a novel aminopeptidase A from the venom of B. g. rhinoceros and highlights its potential biological importance. Similar to mammalian aminopeptidases, rhiminopeptidase A might be capable of playing roles in altering the blood pressure and brain function of victims. Furthermore, it could have additional effects on the biological functions of other host proteins by cleaving their N-terminal amino acids. This study points towards the importance of complete analysis of individual components of snake venom in order to develop effective therapies for snake bites.